Comparison of microbiomes in ulcerative and normal mucosa of recurrent aphthous stomatitis (RAS)-affected patients - Zhongjun Yang; Qingyu Cui; Ran An; Juan Wang; Xiaobo Song; Yu Shen; Mingyu Wang; Hai Xu (BMC, 2020)
Abstract Background Recurrent aphthous stomatitis (RAS) is the most common form of oral ulcerative disease, whose cause is still unknown. Researchers have found the association of many factors with the occurrence of RAS, and proposed oral bacterial infection could be a cause for this disease. Methods To investigate whether the occurrence of RAS is associated with oral bacterial infection, we performed high throughput sequencing analysis of bacterial samples collected from the normal oral mucosa and aphthous ulcers of 24 patients. Results Firmicutes, Proteobacteria and Bacteriodetes were the most abundant phyla in the microbiomes analysed. The alpha diversities of the oral mucosa and aphthous ulcer microbiomes were similar, suggesting a similar richness and diversity. The NMDS analysis showed the oral mucosa and aphthous ulcer microbiomes are significantly different. This suggestion is further supported by Anosim, MRPP, and Adonis analyses. More detailed comparison of the two groups of microbiomes suggested that the occurrence of RAS is significantly associated with the increase of Escherichia coli and Alloprevotella, as well as the decrease of Streptococcus. Conclusions Considering E. coli is a very common intestinal bacterium, we propose that E. coli colonization could be a cause for RAS, and controlling E. coli colonization could help curing RAS.